Urinary excretion of nitric oxide, cyclic GMP, and catecholamines during rest and activity period in transgenic hypertensive rats - Globig, Susanne; Witte, Klaus; Lemmer, Björn (Chronobiology international, 1999)
Dysregulation of the system of nitric oxide (NO)-cyclic 3',5'-guanosine monophosphate (cGMP) might be involved in the development of hypertension in transgenic hypertensive TGR(mREN2)27 (TGR) rats. The present study was performed to determine possible differences in the day-night pattern and the urinary excretion rates of NO and cGMP in TGR rats in comparison to normotensive Sprague-Dawley (SPRD) controls. In addition, the urinary excretion of creatinine and catecholamines was measured in both rat strains. The day-night excretion patterns of NO, cGMP, catecholamines, and creatinine were preserved in TGR rats. Urinary excretion of NO was significantly decreased in TGR rats, whereas cGMP, the second messenger of NO, was elevated in the transgenic animals. Catecholamines and creatinine excretion rates did not differ between the strains. In conclusion, data suggest that a reduced NO synthesis could contribute to the increased blood pressure in the severely hypertensive rats. However, these data make it unlikely that the disturbances in the nitric oxide-cGMP system and the sympathetic nervous system are mainly responsible for the inverse circadian blood pressure rhythm in TGR rats.
Elektronische Reproduktion der Druck-Ausgabe
Published online: 07 Jul 2009
Gesehen am 28.04.2022